A study on the effectiveness of using high temperature to control stored product insects on stored rice grain / Normazura Ismail - Ismail, Normazura (Faculty of Plantation and Agrotechnology, 2018)
Lethal temperature of 80°C was used to decease stored product insects which are Sitophilus oryzae, Tribolium casteneum, and Oryzaephilus surinamensis on rice grain. This laboratory experiment was done to verify the effectiveness of lethal temperature and duration of heat treatment to kill all the population. By using an oven, milled rice with the test insects was used for the heat treatment and each treatment undergone 15 minutes duration of exposure. The number of dead insects, duration of treatments and effects on eating quality of the cooked rice was observed at the end of the treatment. Duration of heat treatment from the studies conducted in laboratory for T. casteneum was respectively five days; O. surinamensis four days; and S. oryzae six days. Based on high resistance S. oryzae, the duration of exposure requires 90 minutes for six days of treatment (15 minutes per day) to kill all 25 adults while the least resistance, O. surinamensis requires 60 minutes. By using an oven, it is recommended 80°C of temperature and 15 to 20 minutes of exposure be adopted to ensure effectiveness against all species in heat treatment. The eating quality of cooked rice in terms of the aroma, stickiness, taste, texture, colour and overall acceptability was not affected from the multiple exposure (3 times) to the heat treatment. Findings from this study indicated heat treatment is a potential replacement for insecticides but it is recommended to use high temperature but in short time of exposure rather than moderate temperature but long time of exposure. Thus, heat treatment can be used for commercial application rice mill producer to control stored product insects during storage phase and milling process.